Hybrid Digital Learning: Enhancing Physical Education Student Achievement in Motor Learning Courses With Synchronous and Asynchronous Session - Fajar Hidayatullah; Khoirul Anwar; Heni Yuli Handayani; Septyaningrum Putri Purwoto; Agus Himawan; Haryo Mukti Widodo (Asosiasi Pengelola Publikasi Ilmiah (APPI) PT PGRI, 2024)
Hybrid digital learning has gained prominence as an innovative approach to enhancing student achievement in motor learning courses within physical education (PE) programs. This study explores the effectiveness of combining synchronous and asynchronous learning sessions to improve students development and performance. In traditional PE courses, students often face challenges in mastering information gained due to the limitations of face-to-face instruction and the varying pace at which individuals learn. The hybrid model, which integrates real-time, instructor-led sessions with flexible, self-paced online learning modules, offers a more dynamic and personalized educational experience. Through synchronous sessions, students benefit from live interaction with instructors, enabling immediate feedback and the opportunity to engage in real-time discussions. Asynchronous sessions, on the other hand, provide students with the flexibility to review course materials, and complete assignments at their own pace, reinforcing learning outside the classroom. This dual approach accommodates different learning styles, encourages self-directed learning, and helps students develop cognitive of motor learning. The study examines the impact of this hybrid learning format on student achievement in motor learning courses, focusing on factors such as cognitive development and student engagement. The findings suggest that students who participated in the hybrid model showed significant improvements in motor skill performance and better retention of learned techniques compared to those in traditional, fully in-person courses. Additionally, the hybrid format promoted greater student self-regulation and allowed for individualized learning, making the course more inclusive and accessible. This research highlights the potential of hybrid digital learning to revolutionize motor learning in physical education, providing a flexible, effective, and engaging approach to developing motor skills and enhancing student outcomes in the digital age.